Improvements in blood transfusion management: cross-sectional data analysis from nine hospitals in Zhejiang, China - Yuanyuan Yao; Jun Li; Mingcang Wang; Zhonghua Chen; Weixing Wang; Lipei Lei; Changshun Huang; Ming Yao; Guihua Yuan; Min Yan (BMC, 2018)
Abstract Background Since 2008, updated perioperative blood management (PoBM) guidelines have been implemented in Zhejiang, China. These guidelines ensure that the limited blood resources meet increasing clinical needs and patient safety requirements. We assessed the effects of implementing updated PoBM guidelines in hospitals in Zhejiang, China. Methods We performed a retrospective multicenter study that included adult patients who received blood transfusions during surgical care in the years 2007 and 2011. The volume of allogeneic red blood cells or autologous blood transfusions (cell salvage and acute normovolemic hemodilution [ANH]) for each case was recorded. The rates of performing appropriate pre-transfusion assessments during and after surgery were calculated and compared between the 2 years. Results We reviewed 270,421 cases from nine hospitals. A total of 15,739 patients received blood transfusions during the perioperative period. The rates of intraoperative allogeneic transfusion (74.8% vs. 49.9%, p <  0.001) and postoperative transfusion (51.9% vs. 44.2%, p <  0.001) both decreased from 2007 to 2011; the rates of appropriate assessment increased significantly during (63.0% vs. 78.0%, p <  0.001) and after surgery (70.6% vs. 78.4%, p <  0.001). The number of patients who received cell salvage or ANH was higher in 2011 (27.6% cell salvage; 9.3% ANH) than in 2007 (6.3% cell salvage; 0.1% ANH). Conclusion Continuing education and implementation of updated PoBM guidelines resulted in significant improvements in the quality of blood transfusion management in hospitals in Zhejiang, China.